Mednarodna klasifikacija funkcioniranja in delovna terapija - Pihlar, Zdenka (Rehabilitacija (Ljubljana), 2008)
International Classification of Functioning, Disability and Health (ICF) is primarily a health and health-related classification ensuring a broader understanding of an individual's functioning in a social environment. It provides support to clinical practice and enables planning of efficient multidisciplinary evidence-based rehabilitation treatment program. The article presents the relation between ICF and occupational therapy model CMOP-E (Canadian Model of Occupational Performance and Engagement) and assessment measure COPM (Canadian Occupational Performance) with emphasis on the evaluation of translatability of the assessment results into ICF codes. Both instruments focus on an individual's functioning in regard to performance and capacity in all areas of human activity taking into account environmental factors affecting the outcome either as facilitators or barriers. The COPM assessment results are translatable into ICF codes. In the Activities and Participation domain all 9 chapters are translatable. The environmental factors most frequently included in COPM are found in chapters 1, 3, 4 and 5.
Keywords: delovna terapija; rehabilitacija; vocational rehabilitation; mednarodna klasifikacija; sodelovanje